ESTABLISHMENT OF THE ELMS LEAF BEETLE XANTHOGALERUCA LUTEOLA (MÜLLER) (COLEOPTERA: CHRYSOMELIDAE) IN CHILE (Acta Entomológica Chilena, 2022)
The invasive establishment of the elm leaf skeletonizing beetle Xantogaleruca luteola (Müller) (Coleóptera: Chrysomelidae) is recorded formally for Chile. The adults are characterized by their external morphology and both sexes genital structure. It is described the damage produced to the ornamental elm trees ans its eventual relationship with Scolytus multistriatus and the Duch elm disease in Chile.
Keywords: Xanthogaleruca luteola, Chrysomelidae, Elm, Pest, Duch elm disease, Chile